Integrative perspectives on human development: dynamic and semiotic - Zittoun, Tania (My University, 2023)
Werner Greve argues for an abstract and integrative theory of development; to progress toward such a theory, he suggests that evolutionary psychology can provide concepts for a processual approach to adaptation. To complement this perspective, I propose to start where the author finishes: the need to further qualify change, and to account for information. Considering ruptures and sense-making as cornerstones of a developmental approach, I recall that open dynamic approaches offer a metatheoretical frame for an integrative developmental psychology, and that cultural approaches already and always account for meaning-making to start with. Assuming these two givens, a variety of integrative propositions account for stability and change; I present an historical example, the work of Gordon Allport, and a current one, our work as sociocultural psychologists, to show how the theoretical and heuristic interest of this proposition.
Keywords: Dynamic sytems; Human development; Lifecourse; Semiotics